2007
DOI: 10.1007/s10549-007-9582-z
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse optical imaging of the healthy and diseased breast: A systematic review

Abstract: Screening X-ray mammography is limited by false positives and negatives leading to unnecessary physical and psychological morbidity. Diffuse Optical Imaging using harmless near infra red light, provides lesion detection based on functional abnormalities and represents a novel diagnostic arm that could complement traditional mammography. Reviews of optical breast imaging have not been systematic, are focused mainly on technological developments, and have become superseded by rapid technological advancement. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
202
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(211 citation statements)
references
References 58 publications
4
202
1
Order By: Relevance
“…Overall, the detection rates we achieved using the DYNOT 232 system are comparable to the detection rates reported for optical imaging in other studies, which are on the order of 85 % [37]. In a study investigating optical imaging of the breast with the contrast agent ICG, Schneider et al reached a sensitivity of 85.7 % and a specificity of 87.5 % for malignant lesions with a time-topeak-based analysis of the amplitude of the increasing signal after ICG injection [6].…”
supporting
confidence: 87%
“…Overall, the detection rates we achieved using the DYNOT 232 system are comparable to the detection rates reported for optical imaging in other studies, which are on the order of 85 % [37]. In a study investigating optical imaging of the breast with the contrast agent ICG, Schneider et al reached a sensitivity of 85.7 % and a specificity of 87.5 % for malignant lesions with a time-topeak-based analysis of the amplitude of the increasing signal after ICG injection [6].…”
supporting
confidence: 87%
“…In a survey of 2000 cases from different studies of optical mammography, Leff et al found that only approx. 85% of malignant lesions were detectable by optical mammography [109]. In this analysis, the type of optical imaging technique used (continuous wave, frequency-domain, or time-domain) appeared to have little effect on diagnostic accuracy [109].…”
Section: Discussionmentioning
confidence: 84%
“…Optical imaging is much more sensitive to smaller amounts of contrast medium than radiographic modalities or MR imaging [22]. Finally, optical imaging has economic advantages: optical scanners are relatively inexpensive to manufacture and operational costs are much lower than for other imaging modalities such as MRI [109].…”
Section: Discussionmentioning
confidence: 99%
“…To provide highly sensitive functional optical contrasts, diffuse optical tomography has been investigated. However, it suffers from poor spatial resolutions [8]. Overall, each modality has notable advantages and limitations.…”
Section: Introductionmentioning
confidence: 99%